Decicion Suport System Pemilihan Pestisida Terbaik Pada UD. Pupuk Jasa Tani Menggunakan Metode Weighted Product - Hezy Kurnia; Vicky Ariandi; Annisak Izzaty Jamhur (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Pesticides are materials to kill pests and diseases in plants. Pesticides are chemicals that are commonly used in agriculture, to kill pests and diseases that exist in agricultural crops. Based on the problems that exist in the community, researchers are trying to help the community to be able to identify the right type of pesticide for the plants that are being planted. Artificial intelligence is transferring the intelligence possessed by humans into a computer machine so that it is able to behave which is considered as intelligent as human abilities. An expert system is a branch of artificial intelligence that transfers the expertise of an expert into a system so that it can imitate the way of thinking of an expert in solving a problem. This expert system application produces output in the form of the best value for selecting the right pesticide based on the criteria inputted by the user and produces conclusions in the form of the best pesticide decision results based on the results of system analysis. The method used in this expert system is the weighted product method which was built using the PHP programming language and MySQL database.